أثر تحرير التجارة الخارجية على الميزان التجاري دراسة حالة الميزان التجاري الجزائري من 2000-2021 - التمالي أحمد; الشيخ بلة عبد الرحيم; لعلا رمضاني (جامعة عمار ثليجي الاغواط, 2022)
The way in which foreign trade sector is regulated varies from one country to another with regard to its economic conditions and the degree of it strength and position at the international level. Similar to other countries, Algeria has got a different policy in this area depending on the economic approach adopted from time to time and the policy it has gone through. The Algerian foreign trade sector, which was marked by dependence on the exports of fuel as a primary source of revenue and on imports of goods and services in supplying the local market since independence to the present day, has had a great impact on various aspects related to trade balance in Algeria. Throughout this study, we sought to identify the reality of the liberalization of foreign trade and its impact on the Algerian trade balance during the period 1990-2015. Despite the measures taken by the country to liberalize its trade in order to increase its exports, its trade balance remains in constant deficit, mainly because of its association with oil revenues, which are considered the primary exports for Algeria.